(untitled) (Research, Society and Development, 2020)
This project was developed as an active learning practice, where Chemical Engineering students, during the Unit Engineering Laboratory course, implemented a Humanitarian Action project, proposing a sustainable response to problems in poor countries through equipment studied in this course. Motivated by the gasoline release tragically occurred in Bogotá, it was proposed to purify the contaminated water by gasoline using adsorption, using a biosorbent with good adsorption efficiency and low cost. The adsorbent used in this work was banana peel, which is an abundant fruit in the country. Thus, in order to evaluate the biomass adsorption capacity, it was obtained the equilibrium isotherm, the adsorption kinetics and the fixed bed column dynamics, constructed from PET bottle. It was possible to adsorb about 1.91 g of gasoline/g of biomass. So, this operation can be a low-cost alternative for the recovery of contaminated aquifers. In addition to the technical report, the students also made an explanatory video in English, to disseminate the knowledge produced to other countries. The students reported that this practice was interdisciplinary, sustainable and technological, developing many competencies and skills necessary for the engineering career.